CD4-CD8-αβ and γδ T Cells Display Inflammatory and Regulatory Potentials during Human Tuberculosis - Pinheiro, Melina B. (Public Library of Science, 2012)
T-cells play an important role controlling immunity against pathogens and therefore influence the outcome of human diseases. Although most T-lymphocytes co-express either CD4 or CD8, a smaller T-cell subset found the in the human peripheral blood that expresses the αβ or γδ T-cell-receptor (TCR) lacks the CD4 and CD8 co-receptors. These double negative (DN) T-cells have been shown to display important immunological functions in human diseases. To better understand the role of DN T-cells in human Mycobacterium tuberculosis, we have characterized their frequency, activation and cytokine profile in a well-defined group of tuberculosis patients, categorized as severe and non-severe based on their clinical status. Our data showed that whereas high frequency of αβ DN T-cells observed in M. tuberculosis-infected patients are associated with disease severity, decreased proportion of γδ DN T-cells are found in patients with severe tuberculosis. Together with activation of CD4(+) and CD8(+) T-cells, higher frequencies of both αβ and γδ DN T-cells from tuberculosis patients also express the chronic activation marker HLA-DR. However, the expression of CD69, an early activation marker, is selectively observed in DN T-cells. Interestingly, while αβ and γδ DN T-cells from patients with non-severe tuberculosis display a pro-inflammatory cytokine profile, characterized by enhanced IFN-γ, the γδ DN T-cells from patients with severe disease express a modulatory profile exemplified by enhanced interleukin-10 production. Overall, our findings suggest that αβ and γδ DN T-cell present disparate immunoregulatory potentials and seems to contribute to the development/maintenance of distinct clinical aspects of TB, as part of the complex immunological network triggered by the TB infection.